Development of tropical cyclones in the Indian Seas as revealed by satellite radiation and television data - SIKKA, D. R. (MAUSAM, 1971)
Nimbus-II Medium. Resolution Infra-red Radiometer (MRIR) and High Resolution Infra-red Radiometer (HRIR) <1;ata ill combination with. ESSA-I television photography is utilised to study the development of a deep depression in the Bay of Bengal during 14 to 17 June 1966. Development of a tropical cyclone in the in the Bay of Bengal and the Arabian Sea during November 1966 IS also followed with the HRIR data and ESSA-3 television pictures: The results of the study show the usefulness of radiation data in determining the extent of the cirrus canopy and its location and determination of the general magnitude of the peripheral subsidence.